2022
DOI: 10.1038/s41431-022-01054-5
|View full text |Cite
|
Sign up to set email alerts
|

Receiving results of uncertain clinical relevance from population genetic screening: systematic review & meta-synthesis of qualitative research

Abstract: Genetic screening can be hugely beneficial, yet its expansion poses clinical and ethical challenges due to results of uncertain clinical relevance (such as ‘cystic fibrosis screen positive, inconclusive diagnosis’/CFSPID). This review systematically identifies, appraises, and synthesises the qualitative research on experiences of receiving results of uncertain clinical relevance from population genetic screening. Eight databases were systematically searched for original qualitative research using the SPIDER fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
(185 reference statements)
0
10
0
Order By: Relevance
“…In a systematic review, Johnson et al. (2022) concluded that uncertain results do not fit into a recognized medical model and that initial communication needs to clearly address this potential outcome of genetic testing to minimize psychological harm. Therefore, learning how to frame uncertainty should be an essential aspect of ICC nurse training.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review, Johnson et al. (2022) concluded that uncertain results do not fit into a recognized medical model and that initial communication needs to clearly address this potential outcome of genetic testing to minimize psychological harm. Therefore, learning how to frame uncertainty should be an essential aspect of ICC nurse training.…”
Section: Discussionmentioning
confidence: 99%
“…For parents, receiving a result of uncertain clinical significance from newborn screening can be distressing, and this negative impact may persist when uncertainty remains unresolved. 39 At the same time, it has been well‐established that pathogenic variants in ABCD1 have no predictive value with respect to clinical outcome. This is a complicating factor in ALD disease management.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of WGS, the range of possible incidental findings, the inevitable uncertainties, and the often limited understanding about genomics by patients, their family, and sometimes by mainstream clinicians can make informed consent difficult to achieve [ 5 , 6 ]. Some have argued that an excess of information can be a deterrent for patients, as it may lead to difficulties in ensuring valid consent and hinder access to potentially valuable investigations and treatments [ 4 , 5 ].…”
Section: Managing Expectations In a Busy Mainstream Clinicmentioning
confidence: 99%